Bimetallic Au–Ag Nanoparticles: Advanced Nanotechnology for Tackling Antimicrobial Resistance - Singh C.; Mehata A.K.; Priya V.; Malik A.K.; Setia A.; Suseela M.N.L.; Vikas M.N.L.; Gokul P.; Samridhi P.; Singh S.K.; Muthu M.S. (My University, 2025)
To date, there are no antimicrobial agents available in the market that have absolute control over the growing threat of bacterial strains. The increase in the production capacity of antibiotics and the growing antibacterial resistance of bacteria have majorly affected a variety of businesses and public health. Bimetallic nanoparticles (NPs) with two separate metals have been found to have stronger antibacterial potential than their monometallic versions. This enhanced antibacterial efficiency of bimetallic nanoparticles is due to the synergistic effect of their participating monometallic counterparts. To distinguish between bacteria and mammals, the existence of diverse metal transport systems and metalloproteins is necessary for the use of bimetallic Au–Ag NPs, just like any other metal NPs. Due to their very low toxicity toward human cells, these bimetallic NPs, particularly gold–silver NPs, might prove to be an effective weapon in the arsenal to beat emerging drug-resistant bacteria. The cellular mechanism of bimetallic nanoparticles for antibacterial activity consists of cell membrane degradation, disturbance in homeostasis, oxidative stress, and the production of reactive oxygen species. The synthesis of bimetallic nanoparticles can be performed by a bottom-up and top-down strategy. The bottom-up technique generally includes sol-gel, chemical vapor deposition, green synthesis, and co-precipitation methods, whereas the top-down technique includes the laser ablation method. This review highlights the key prospects of the cellular mechanism, synthesis process, and antibacterial capabilities against a wide range of bacteria. Additionally, we also discussed the role of Au–Ag NPs in the treatment of multidrug-resistant bacterial infection and wound healing. © 2022 by the authors.